Pisces, Perciformes, Cichlidae, Laetacara dorsigera (Heckel, 1840): distribution extension and first record for Uruguay River basin, and state of Rio Grande do Sul, southern Brazil - Luis Lanés; Leonardo Maltchik; Carlos Lucena (Check List, 2010)
The present study records for the first time the small cichlidae fish Laetacara dorsigera (Heckel, 1840) at Uruguay River basin and state of Rio Grande do Sul, southern Brazil, previously known from Amazon, Paraná and Paraguay River basins. Although the ichthyofauna of Uruguay River basin is relatively well known, this record suggests that there are still unexplored environments, such as wetlands, where there may be species not yet reported, and found in other hydrographic systems.